2021
DOI: 10.1002/jts.22680
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Brief Family Intervention to Reduce Dropout Among Veterans in Individual Trauma‐Focused Treatment: A Randomized Controlled Trial

Abstract: Dropout from trauma‐focused treatment for posttraumatic stress disorder (PTSD) represents a daunting challenge for the field, particularly among military and veteran samples. Family involvement may help to increase the effectiveness of PTSD treatment while also improving retention. We tested a two‐session brief family intervention (BFI) protocol delivered as an adjunct to individual trauma‐focused treatment among a sample of 20 veteran–family member dyads (N = 40). Willingness to participate in the family‐incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 54 publications
2
40
0
Order By: Relevance
“…Observational research shows close relationships play a critical role in stimulating veterans’ treatment-seeking behavior [ 66 , 67 ] and family encouragement reduces PTSD treatment dropout [ 15 ]. Lastly, Thompson-Hollands and colleagues [ 14 ] reduced treatment dropout by 20% when family members were randomized to participate in a two-session adjunctive intervention versus when veterans participated in standard TFT [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational research shows close relationships play a critical role in stimulating veterans’ treatment-seeking behavior [ 66 , 67 ] and family encouragement reduces PTSD treatment dropout [ 15 ]. Lastly, Thompson-Hollands and colleagues [ 14 ] reduced treatment dropout by 20% when family members were randomized to participate in a two-session adjunctive intervention versus when veterans participated in standard TFT [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment adherence is infrequently a target of family-involved interventions. However, in a recently completed small RCT ( n = 40), Thompson-Hollands and colleagues [ 14 ] found that a two-session adjunctive intervention with family members, as veterans began PE or Cognitive Processing Therapy (CPT), reduced treatment dropout by 20%, compared to standard PE or Cognitive Processing Therapy. Additionally, Meis and colleagues [ 15 ] found that when veterans entering either PE or CPT were encouraged by a close loved one to face things that made them anxious and uncomfortable, they were more than twice as likely to finish one of these TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…Families remain an underutilized resource within VHA, despite clear indications that veterans desire family involvement (e.g., Batten et al, 2009 ) and preliminary evidence that family inclusive care may offer a bolstering effect to trauma-focused treatment (Thompson-Hollands et al, 2021b ). Our results suggest that there are multiple avenues that could be pursued to more emphatically promote family involvement in care.…”
Section: Discussionmentioning
confidence: 99%
“…EBPs are the treatments that have the most evidence for meaningfully reducing PTSD symptoms (U.S. Department of Veteran Affairs and Department of Defense, 2017), and they must be prioritized. However, accumulating evidence suggests that certain family member behaviors (Meis et al, 2019;Sayer et al, 2017), or the incorporation of families into treatment (Thompson-Hollands et al, 2021b), enhances treatment retention in CPT and PE and therefore that these approaches may strengthen rather than detract from EBPs. For clinicians looking to increase their use of family involvement to support EBPs there are several lower-intensity protocols available, including Veteran-Centered Brief Family Consultation (U.S. Department of Veterans Affairs, 2018; VA Family Services) and the Brief Family Intervention for PTSD (Thompson-Hollands et al, 2021c;Thompson-Hollands et al, 2021b); both are specific to veterans and typically range from 1 to 3 sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation